A preoperative metabolic marker of parkinsonian apathy following subthalamic nucleus stimulation. Issue 13 (31st July 2015) - Gesquière‐Dando, Aude; Guedj, Eric; Loundou, Anderson; Carron, Romain; Witjas, Tatiana; Fluchère, Frédérique; Delfini, Marie; Mundler, Laura; Regis, Jean; Azulay, Jean‐Philippe; Eusebio, Alexandre
Abstract: Background: Subthalamic nucleus deep brain stimulation (STN‐DBS) in Parkinson's disease (PD) has been associated with the development of postoperative apathy. Debate on the causes of postoperative apathy continues, and the dominant hypothesis is that stimulation or dopaminergic drug reductions are causal in its development. We hypothesized that a preoperative predisposition to apathy also could exist. To this end, we sought to identify a preoperative metabolic pattern using [ 18 ]Fluorodeoxyglucose Positron Emission Tomography (PET), which could be associated with the occurrence of postoperative apathy after STN‐DBS for PD. Methods: Thirty‐four patients with PD, not clinically apathetic, underwent an [ 18 ]Fluorodeoxyglucose‐PET scan before surgery of STN‐DBS, and were tested for the occurrence of apathy 1 y after surgery. Whole‐brain voxel‐based PET intergroup comparison ( P < 0.005; corrected for the cluster) was evaluated between patients who developed apathy at 1 y and those who did not. Results: Eight patients (23.5%) became apathetic after surgery. Motor improvement and decrease in dopaminergic treatment were similar in both postoperative apathy and non‐apathy groups. We found a cluster of significantly greater metabolism in the postoperative apathy group within the cerebellum, brainstem (in particular ventral tegmental area), temporal lobe, insula, amygdala, lentiform nucleus, subgenual anterior cingulate, and inferior frontal gyrus. A metabolic value above 68 could discriminate patients who would develop postoperative apathy with 100% sensitivity and 88.5% specificity. Conclusions: We describe a preoperative metabolic pattern associated with the development of apathy after STN‐DBS in PD. This suggests the existence of a predisposition to apathy, which may further be triggered by perioperative drug modifications. © 2015 International Parkinson and Movement Disorder Society